Unsteady melt heat flow coupling optimization method for sapphire crystal seeding growth by the Kyropoulos method. Issue 14 (16th March 2022) - Xu, Jia; Qiao, TieZhu; Li, Qing; Zhang, GuoWei; Hao, GuiRong
Abstract : The optimization method of crystal rotation can effectively improve the temperature distribution on the surface of the melt. Abstract : High-quality seeding is the key to ensure the preparation of high-quality sapphire single crystals. The strength and direction of the melt flow control the crystal seeding shape and bubble movement and will directly affect the quality of crystal seeding. To improve the crystal seeding quality under complex convection, based on the lattice Boltzmann method, an optimization method of seed crystal rotation was proposed before crystal seeding, and the unsteady melt flow rate, internal temperature of the melt and crystal rotation speed were calculated and analyzed. The coupling relationship between the Grashof number and the Reynolds number is analyzed. The results show that the optimization method of crystal rotation can effectively restrain the convection of the melt and improve the temperature distribution on the surface of the melt. Compared with the multi-frame intercomparison visual inspection detection method and artificial seeding method, the method proposed in this paper is helpful to improve the quality of sapphire seeding.